Pancreatic walled off necrosis extending along portal vein tract: A rare complication of severe necrotizing pancreatitis. - Debi, Uma; Nagpal, Anoop; Singh, Lokesh; Rana, Surinder (Indian Journal of Case Reports, 2019)
-